EXPLORING THE FACTORS THAT CAN STIMULATE FAN ENGAGEMENT IN CONDITIONS OF LOW SPORTS PERFORMANCE - SANDU VLAD ANTONIUS; POPESCU MARIUS CĂTĂLIN; COSTIN DAN EUGEN; PĂSĂRIN LEONARDO DANIEL; POPA MARIAN GABRIEL (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
In the digital age we live in today, fan engagement is more important than ever. With so many distractions competing for people's attention online, teams and athletes must find ways to capture the attention of their fans. Professional sports would not exist without engaged fans as we know it today. In the paper "Exploring the factors that can stimulate fan engagement in conditions of low sports performance" we begin with a brief description of this phenomenon of fan engagement and its importance within any sports organization, and how fans have had to keep up with the digital age. In the end, a small study is presented on the factors that contribute to maintaining the relationship with the fans even when the team or the athlete has a period with lower performances.